Minuman Ringan Berkarbonasi Dapat Meningkatkan Keasaman Rongga Mulut - Ni Putu Widani Astuti; Tri Purnami; Cok Gede Agung Kusuma Putra (Faculty of Dentistry, Mahasaraswati Denpasar University, 2018)
Soft drinks are beverages that do not contain alcohol (non alcoholic). Soft drinks have a low pH (<5.5). Consuming carbonated soft drinks can cause increased acidity in the oral cavity. The acidity of the oral cavity occurs due to disruption of the saliva buffer system whose function is to resist the decrease in pH or increase the acidity of the oral cavity. The purpose of this study was to determine the effect of carbonated soft drinks on the acidity of the mouth. Type of research used in this study was quasi-experimental with a pre-test post-test design group approach. This study used a sample of 50 people by using random sampling techniques. All samples consisting of 50 people were asked to accommodate the saliva first and then measured with a pH meter. After that, all samples were instructed to drink soft drinks according to the specified dose (250ml). Five minutes later all samples were asked to collect the saliva again and then measure it. The results obtained from this study are based on a T-test where the level of significance produced is smaller than 0.05 which states that carbonated soft drinks have a significant effect on the acidity of the oral cavity. The conclusion is carbonated soft drinks can increase the acidity of the oral cavity.